Models of care for the delivery of secondary fracture prevention after hip fracture : a health service cost, clinical outcomes and cost-effectiveness study within a region of England /: a health service cost, clinical outcomes and cost-effectiveness study within a region of England. (September 2016) - Judge, Andrew David
No abstract available